Correlation between acoustic emission distribution and stress variation through the depth of RC beam cross sections. (30th September 2017) - Liu, Simeng; Pearson, Matthew R.; Eaton, Mark; Pullin, Rhys
Highlights: The acoustic emission distribution through the depth of RC beam sections is studied. AE parameters can characterise behaviours of RC beams in the depth direction. AE event intensity shows a higher correlation than energy-based parameters in the study. The correlation between AE and stress responses was demonstrated to be very strong. A new option for estimating stress levels in engineering and science is considered. Abstract: Two established techniques for monitoring concrete under loading are Acoustic Emission (AE) and strain gauges. The distribution of strain, along with that of stress, on a beam cross section is well established both theoretically and experimentally. However, the AE distribution through the depth of the cross section has received little attention previously. In addition, the correlation between the AE distribution and that of stress on the section could provide valuable insight into the condition of a structure. Therefore, these topics are experimentally addressed in this article. Specifically, six Reinforced Concrete (RC) beams were tested. AE and Digital Image Correlation (DIC) were employed to monitor the beams during loading. Finally, the AE and stress distributions were analysed. The results showed that AE parameters are capable of characterising behaviours of RC beams in the depth direction. Furthermore, the distribution of AE events strongly correlated with that of compressive stress, especially in the post-reinforcement yielding stage. According to these findings, it is highly possible to estimate stress levels of RC beam structures in engineering and science by adopting the AE technique.